1993
DOI: 10.1111/j.1365-2044.1993.tb07129.x
|View full text |Cite
|
Sign up to set email alerts
|

The Finapres 2300e finger cuff

Abstract: SummaryBlood pressure measurements associated with malapplication of a finger cuff were compared with contemporaneous intra-arterial pressure data in seven volunteers to determine the influence of cuff application on the accuracy of the Finapres 2300e. Systolic readings in all cuff positions differed from arterial line data by more than the recommended standard and tight and loose cuff applications under and over-read respectively, in all subjects. The results show the Finapres to be sensitive to small degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The large interindividual variability may partly explain the wide range of biases (underestimation of intra‐arterial pressure in some patients and overestimation in others). It may reflect both technical, physiological and pathological influences (disease states affecting peripheral blood flow, presence of a pressure gradient) [ 6, 15, 26]. A study [ 6] compared the accuracy between different cuff sizes, cuff positions and choice of finger and showed that the thumb gives the most accurate results (correlation coefficients of 0.95 for systolic and 0.88 for diastolic blood pressure vs values obtained invasively).…”
Section: Resultsmentioning
confidence: 99%
“…The large interindividual variability may partly explain the wide range of biases (underestimation of intra‐arterial pressure in some patients and overestimation in others). It may reflect both technical, physiological and pathological influences (disease states affecting peripheral blood flow, presence of a pressure gradient) [ 6, 15, 26]. A study [ 6] compared the accuracy between different cuff sizes, cuff positions and choice of finger and showed that the thumb gives the most accurate results (correlation coefficients of 0.95 for systolic and 0.88 for diastolic blood pressure vs values obtained invasively).…”
Section: Resultsmentioning
confidence: 99%
“…However, some situation-or procedurerelated errors are not uncommon [13,14]. For example, patients with acrocyanosis are less suitable for Finapres or Portapres recordings.…”
Section: Resultsmentioning
confidence: 99%
“…Lights off 2300 to 0700 h. Black dots, first recording; open dots, second recording. of procedure-related errors have been identified [13,14]. Cold fingers and malapplication of the cuff may cause important errors and reduce repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the excessively small cuff was not appropriate for arterial elasticity analyses using the AC signal of PPG. Meanwhile, Jones et al claimed that the oversize cuff was less accurate for assessments of PPG 35. Moreover, if the oversize cuff was loosely applied to a finger, the P c could have been ineffectively transmitted to the finger, resulting in an overestimation of the mean blood pressure.…”
Section: Discussionmentioning
confidence: 99%